Hydrocephalus : What do we know? And what do we still not know? - Ammar, Ahmed (Springer International Publishing : Imprint: Springer, 2017)
This book provides the reader with a well-structured, comprehensive approach to hydrocephalus and related syndromes. It also addresses the ethical dilemmas of managing hydrocephalus, of which many neurosurgeons are unaware, and presents cutting-edge research genetic and pathophysiology research on hydrocephalus. The book presents a new classification for the Dandy Walker syndrome, based on a new understanding of different hydrocephalic problems. Further, it puts forward a wholly new theory on the pathophysiology and development of multiloculated hydrocephalus. This book helps the reader to devise a long-term strategic plan to treat patients, based on research of favorable long-term outcomes of hydrocephalus. It uniquely provides evidence-based approaches to managing hydrocephalus, presenting the experience and thoughts of renowned and highly experienced neurosurgeons from the USA, Canada, Japan, Europe and the Middle East.
Keywords: Medicine.; Neurosciences.; Bioethics.; Neurology.; Neurosurgery.; elektronické knihy; electronic books